Comparing protected cucumber and field cucumber production systems in China based on emergy analysis. (1st November 2019) - Zhao, Huan; Zhai, Xiajie; Guo, Lizhu; Yang, Yuejuan; Li, Jiahuan; Ren, Cheng; Wang, Kaili; Liu, Xiqiang; Zhan, Ruyi; Wang, Kun
Abstract: Cucumber is an important vegetable, which provides essential minerals, vitamins and nutrients for human body and is widely cultivated in China on account of its delicious taste, short nutritional cycle and high economic benefits. To comprehensively evaluate the sustainability of the cucumber production systems under two planting patterns (the protected cucumber production system and the field cucumber production system), and to provide constructive suggestions for an efficient and sustainable development of the production systems, the emergy evaluation method was utilized to analyze the composition and metabolism of the emergy flows in the production systems based on 2016 provincial data from China. The results show that the mean value of natural resources input of the field cucumber production system (13.59E+14 sej/ha) was significantly higher than that of the protected cucumber production system (5.92E+14 sej/ha). However, the mean values of the purchased resources input, total emergy input and total energy output had the contrary trend. The extent to which the cucumber production systems under two planting patterns are dependent on the environment is different. The field cucumber production system uses more natural resources and the degree of utilization of natural resources is geographically distributed. More natural resources are utilized in the south of China where natural conditions are better. However, the protected cucumber production system uses more purchased resources, especially the nonrenewable resources, and has the characteristics of high input, high output but low production efficiency. Improving the efficiency of resources utilization, using more clean energy and improving the degree of mechanization will contribute to a cleaner, more efficient and sustainable development of the cucumber production system. Highlights: The extent to which the two systems are dependent on the environment is different. Field cucumber system uses more natural resources in places with better natural conditions. Protected cucumber system uses more purchased resources, especially nonrenewable resources. Together natural resources and purchased resources maintain cucumber production systems. Protected cucumber system is of high input, high output but low production efficiency.